Tip coupling and array effects of gold nanoatennas in near-field microscopy - Büchner,R; Weber,T; Kühner,L; Maier,SA; Tittl,A (ACS Photonics, 2021)
Scattering-type scanning near-field optical microscopy (s-SNOM) is one of the predominant techniques for the nanoscale characterization of optical properties. The optical response of nanoantennas in s-SNOM is highly sensitive to their environment, including influences of the probing tip or neighboring resonators. Dielectric tips are commonly employed to minimize tip-related perturbations, although they provide a comparatively weak scattering signal. Here we show that when using metallic tips, it is possible to select between distinct weak and strong tip–antenna coupling regimes by careful tailoring of the illumination conditions and resonator orientation. This enables the use of highly scattering metallic instead of dielectric tips for mapping plasmonic modes with comparatively higher signal strengths. This is a particular advantage for the retrieval of near-field spectra, which simultaneously require high near-field signals and unperturbed field patterns. We leverage our approach to analyze the collective effects of nanoantenna arrays, phenomena that are well understood in the optical far-field but have not been extensively studied in the near-field. Probing the dependence of the optical response on the array field size, we identify three regimes: the single rod regime, the intermediate regime, and the array-like regime. We show that these array effects give rise to characteristic spectral features originating from a complex interplay of radiative coupling and plasmon hybridization. These results provide evidence that long-range interactions of antennas also influence the local optical response that is probed in s-SNOM and demonstrate how collective resonances emerge from single building blocks, providing guidelines for optimized array designs for near- and far-field applications.